2013
DOI: 10.1124/mol.112.083519
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular Dilation via Selective Targeting of the Cholane Steroid-Recognition Site in the BK Channel β1-Subunit by a Novel Nonsteroidal Agent

Abstract: The Ca 21 /voltage-gated K 1 large conductance (BK) channel b1 subunit is particularly abundant in vascular smooth muscle. By determining their phenotype, BK b1 allows the BK channels to reduce myogenic tone, facilitating vasodilation. The endogenous steroid lithocholic acid (LCA) dilates cerebral arteries via BK channel activation, which requires recognition by a BK b1 site that includes Thr169. Whether exogenous nonsteroidal agents can access this site to selectively activate b1-containing BK channels and ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
52
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 60 publications
(96 reference statements)
7
52
0
Order By: Relevance
“…Rats and mice were decapitated using a guillotine and sharp scissors, respectively. Middle cerebral arteries (,260 mm and ,150 mm external diameter in rat and mouse species, respectively) were isolated and cannulated as described in our earlier work (Bukiya et al, 2013). When required, endothelium was removed by passing an air bubble into the vessel lumen for 90 seconds before vessel cannulation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rats and mice were decapitated using a guillotine and sharp scissors, respectively. Middle cerebral arteries (,260 mm and ,150 mm external diameter in rat and mouse species, respectively) were isolated and cannulated as described in our earlier work (Bukiya et al, 2013). When required, endothelium was removed by passing an air bubble into the vessel lumen for 90 seconds before vessel cannulation.…”
Section: Methodsmentioning
confidence: 99%
“…In all experiments where ethanol in solution was applied to tissues, solutions with urea isosmotically replacing for ethanol were used as control solution (Liu et al, 2004). Pial arteriolar diameter was monitored with a video micrometer coupled to a television camera that depicted the brain surface through the cranial window (Bukiya et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…[13, 14] Cholane steroids such as the bile acid, lithocholic acid (LCA), increase BK Ca channel activity through interaction with β 1 subunits. [14] This action is β 1 subunit-specific and not observed with β 2-4 subunit-containing BK Ca complexes or with homomeric α channels.…”
Section: Introductionmentioning
confidence: 99%
“…[16] Previous structure-activity relationship (SAR) studies indicated that the overall shape of the bile acid, as well as the number of hydroxyls, and placement of hydroxyls and carboxylic acids, were important in bile acid interaction with β 1. [14] Among non-steroidal compounds, only one triterpenoid, 3-hydroxyolean-12-en-30-oic acid (3-HENA)[13] has been reported to specifically target β 1 -containing BK Ca complexes. Moreover, although there are several ligands with β 1 -dependent effects on BK Ca channel opening, only LCA and 3-HENA have been reported to interact with a defined recognition site [13] making the other ligands less useful in determination of a pharmacophore.…”
Section: Introductionmentioning
confidence: 99%
“…T169A has been proven to serve as a screening tool to identify possible ligands for the BK ␤1 TM2 domain steroidsensing site (12,30). Successful expression of ␤1T169A and its presence within the channel complexes were validated by detecting the ␤1 subunit-characteristic phenotype of cbv1-␤1T169A macroscopic current (12).…”
Section: Ltb4 But Not Other Leukotrienes Of the Lt4mentioning
confidence: 99%